Comparison of local distortions in Ba8Ga16X30 (X = Si, Ge, Sn): an EXAFS study. Issue 40 (17th August 2015) - Keiber, Trevor; Nast, Patrick; Medling, Scott; Bridges, Frank; Suekuni, Koichiro; Avila, Marcos A.; Takabatake, Toshiro
Abstract : We report an extended X-ray fine structure (EXAFS) analysis of the type-I clathrates Ba8 Ga16 X30 (X = Si, Sn) and compare the results with the results of previous studies on X = Ge. The environment about Ba is the most disordered for X=Sn. Abstract : We report an extended X-ray fine structure (EXAFS) analysis of the type-I clathrates Ba8 Ga16 X30 (X = Si, Sn) and compare the results with the results of previous studies on X = Ge. The distribution of Ga on the three crystallographic cage sites is not random, with the Ga preferentially having X as the nearest neighbor. Our results show that for X = Si, Sn the average pair distances within the cages (Ga–Sn, Ga–Ga, Ga–Si, Sn–Sn) are significantly different from the distances found in X-ray diffraction, with some much shorter bonds and some much longer bonds. These results suggest a substantial buckling of the cages, particularly for Ba8 Ga16 Sn30 . The environment about Ba, extracted from Ba K edge EXAFS, becomes increasingly disordered from Ge to Si to Sn, and for Ba8 Ga16 Sn30 the nearest Ba neighbor distance is very short, consistent with severe buckling. This buckling contributes to the increased local disorder for Ba8 Ga16 Si30 and Ba8 Ga16 Sn30, and provides an explanation for a higher resistivity and a lower ZT than for Ba8 Ga16 Ge30 .